2021
DOI: 10.1108/cms-09-2020-0387
|View full text |Cite
|
Sign up to set email alerts
|

Subordinates’ negative workplace gossip leads to supervisor abuse: based on the conservation of resources theory

Abstract: Purpose Based on the conservation of resources (COR) theory, this paper aims to explore the potential influence of perceived subordinates’ negative workplace gossip on abusive supervision in China. Moreover, the COR theory helps in examining the mediating role of self-esteem threat and psychological distress and the moderating role of mindfulness on the effects of perceived subordinates’ negative workplace gossip on abusive supervision. Design/methodology/approach Data was collected from 305 supervisor-subor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(145 reference statements)
0
9
1
Order By: Relevance
“…Supervisor incivility can damage employees' organizational loyalty, job and life satisfaction and increase work-life conflict and intention to resign (Tepper, 2000;Guchait et al, 2023). Moreover, supervisor incivility intensifies workplace gossip (organizational gossip; Ye et al, 2022), ego depletion and intention to quit (Yin et al, 2023), being silenced (Srivastava et al, 2023), job insecurity (Khalid et al, 2022) and employees' psychological distress (Dedahanov et al, 2022), well-being (Kuriakose et al, 2022) and diminishes self-respect and psychological distress (Ye et al, 2022).…”
Section: Supervisor Incivilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Supervisor incivility can damage employees' organizational loyalty, job and life satisfaction and increase work-life conflict and intention to resign (Tepper, 2000;Guchait et al, 2023). Moreover, supervisor incivility intensifies workplace gossip (organizational gossip; Ye et al, 2022), ego depletion and intention to quit (Yin et al, 2023), being silenced (Srivastava et al, 2023), job insecurity (Khalid et al, 2022) and employees' psychological distress (Dedahanov et al, 2022), well-being (Kuriakose et al, 2022) and diminishes self-respect and psychological distress (Ye et al, 2022).…”
Section: Supervisor Incivilitymentioning
confidence: 99%
“…Empirical research has shown that organizational gossip is associated with anger and shame (Zong et al , 2023), perceived organizational politics, compassion (Khan and Chaudhary, 2023), employees’ mental health and psychological capital (Cheng et al , 2023). Organizational gossip has a negative relationship with organizational identity (Xie et al , 2022) and threat to self-respect and a positive relationship with supervisor civility and psychological distress (Ye et al , 2022). Concurrently, there is a positive relationship between gossip and supervisor incivility and psychological distress, and a negative relationship with threat to self-respect (Ye et al , 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “resources” is broadly defined in the COR theory, such that it captures any “objects, personal characteristics, conditions, or energies that are valued in their own right, or that are valued because they act as conduits to the achievement or protection of valued resources” (Hobfoll, 2001, p. 339). Yet a particularly pertinent resource, highly treasured by employees, according to Hobfoll’s (2001) influential theorizing and subsequent studies (Bentein et al , 2017; Ye et al , 2022), is organization-based self-esteem or the extent to which they have a positive image of themselves in relation to their work. But employees exposed to dysfunctional organizational politics suffer a diminished work-related sense of self-worth, because they feel excluded from decision-making processes and experience job uncertainty (De Clercq and Pereira, 2022b; Hasan et al , 2019).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The reasons leaders abuse their subordinates are mainly explored using two perspectives from the subordinate level (e.g., provocative behavior, anti-productive work behavior, high dependence, self-interest, passivity, and negative workplace gossip) (Tepper and Simon, 2015;Ye et al, 2021) and organizational level (e.g., poor relationships, negative organizational climates, and low organizational fairness) (Hoobler and Hu, 2013;Zhang and Bednall, 2016). However, researchers have recently turned their attention to investigating the antecedents of abusive supervision from supervisor-focused factors, such as supervisor traits or experiences (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%